The faces of the oil palm :the relevance of the oil palm agro-industry in Colombia (Federación Nacional de Cultivadores de Palma de Aceite - FEDEPALMA, 2007)
Much is said about the oil palm, but few people stop to ask what this crop means to Colombia and to its people. The furthest experts go is to point out that we are witnessing a highly successful example of agricultural development, an agro-industry which is the main provider of raw materials for the production of edible fats and oils, soaps and other derivative products. Too frequently, these people neglect to highlight something which defines the oil palm-growing industry in Colombia: that for over 50 years it has been shaped by Colombian entrepreneurs, farmers, and workers, and that it is an economic activity with deep social and territorial roots, through which whole communities play out their daily lives, and therefore, an axis around which their identity and sense of belonging revolve.